3D-printed POF insole: Development and applications of a low-cost, highly customizable device for plantar pressure and ground reaction forces monitoring. (August 2019) - Leal-Junior, Arnaldo G.; Díaz, Camilo R.; Marques, Carlos; Pontes, Maria José; Frizera, Anselmo
Highlights: POF-embedded 3D printed insole for gait analysis. Multiplexing technique for 15 pressure sensors in a single fiber. Experimental validation for ground reaction force, center of pressure and pressure map. Applications in gait analysis of 20 healthy subjects and validation on a force platform. Abstract: This paper presents the development, characterization and application of a 3D-printed instrumented insole with polymer optical fiber (POF) sensors for static and dynamic assessments of plantar pressure and ground reaction force (GRF). The proposed insole has 15 intensity variation-based sensors multiplexed in a single POF using a time-domain multiplexing technique based on side-coupling between the light sources and POF lateral sections. The proposed insole was validated in dynamic and static tests compared with a commercial force platform. Results show a high correlation between the proposed insole and the force platform on GRF measurements and in the assessment of bidirectional displacement of the center of pressure. The correlation coefficient between the proposed 3D-printed insole and the platform was higher than 0.87 for all subjects and tests. In addition, the ability of detecting gait events and estimating users' body mass were evaluated with errors lower than 3.4% for tests with 20 subjects. The proposed insole presents additional advantages of low cost, high portability and high degree of customizability, since the insole can be easily fabricated with personalized sizes and optimized sensors positions, which is regarded as an important asset for human-in-the-loop design of wearable devices for clinical evaluation and remote health monitoring.